Manejo de profilaxis antibiótica en los pacientes con patología traumatológica atendidos en el departamento de Cirugía del hospital General Isidro Ayora Loja durante el periodo julio-noviembre de 2013. - León Ojeda, Diego Fabián. (2014)
The surgical site infections are a source of concern for the orthopedic surgeon to be difficult to resolve, the antibiotic chosen in a suitable dose and the time reveals a good surgical prophylaxis. This work is descriptive and aims to meet the management of antibiotic prophylaxis in trauma patients treated at the pathology department of surgery Isidro Ayora Hospital Loja during July-November 2013, for which collected data from the medical records of patients undergoing orthopedic surgery on a data collection sheet , then the results indicate that the antibiotic most used for cefazolin prophylaxis , the first dose is given during surgery in only half of patients and the second dose after 10 hours , lasting more than 24 hours in most cases, and the presence of surgical wound infections of 8.13 %, which is plotted in statistical tables and the discussion is set, conclusions and recommendations. Key words: Antibiotic, surgery, infection